Influence of excesses of volatile elements on structure and composition of solution derived lead-free (Bi0.50Na0.50)1xBaxTiO3 thin films. Issue 1 (January 2016) - Pérez-Mezcua, D.; Calzada, M.L.; Bretos, I.; Ricote, J.; Jiménez, R.; Fuentes-Cobas, L.; Escobar-Galindo, R.; Chateigner, D.; Sirera, R.
Abstract The preparation of (Bi0.50Na0.50)1−xBaxTiO3 films requires a compositional/structural control, as they determine the functionality of these materials. We report a systematic compositional and structural analysis on (Bi0.50Na0.50)1−xBaxTiO3 films fabricated by chemical solution deposition. The effects of incorporating Na(I) and Bi(III) excesses are analyzed through the comparison of the compositional depth profiles of stoichiometric films (BNBT) and films containing excesses (BNBTxs). Heterogeneous compositional profiles with larger bismuth content close to the substrate and thicker film-substrate interfaces are observed in BNBTxs, unlike stoichiometric films, which show atomic concentrations that correspond to the nominal composition of the precursor solution. Excesses induce structural differences in depth, observing a shift of the region of coexistence of rhombohedral and tetragonal phases (morphotropic phase boundary) toward higher x values and the formation of thick film-substrate interfaces. In contrast, stoichiometric films have homogeneous compositional and structural profiles with the MPB placed close to that described for bulk ceramics.